Genetic Diversity and Relationships among Sugarcane (Saccharum sp.) from Thailand Revealed by RAPD and AFLP Markers - Supattra Poeaim; Ailada Chaiyabut; Anurug Poeaim; Kasedis Distabanjong (My University, 2017)
Objective: The objective of the present research was to evaluate the genetic diversity and relationships of sugarcane (Saccharum sp.) that collected from the sugarcane germplasm collection, Thailand. Methods: Genetic diversity of sugarcane was detected by DNA sequencing, Random Amplified Polymorphic DNA (RAPD) and Amplified Fragment Length Polymorphism (AFLP) markers. Findings: The trnL- trnF region of the chloroplast genome was amplified for 26 cultivars with C and F primers that the fragment was approximately 950 base pairs (bp). The taxonomic status and relationships of these sequences are not resolved. RAPD marker was used to study genetic variation and relationships among 56 sugarcane varieties and their hybrids. Ninety-six RAPD primers were screened and nine primers of them produced reproducible and recordable bands were used in analysis. The eighty-eight polymorphic bands (96.70%) were detected and genetic similarity was 0.657. The best five AFLP primer combinations were selected and generated 187 polymorphic bands (80.26%). Comparing the results from the RAPD and AFLP markers in 19 sugarcane cultivars, the genetic similarity ranging from 0.582 to 0.927, with the average of 0.756 for AFLP and ranging from 0.449 to 0.865, with the average of 0.657 for RAPD that demonstrating a low level of genetic diversity. For dendrogram analysis, AFLP marker showed itself to be more efficient at discriminating sugarcane cultivars. However, the genetic relationship of the samples slightly correlated with sucrose content. Application: RAPD and AFLP markers can be used to help plant breeder to select cultivars for future sugarcane improvement programs. Keywords: AFLP, Genetic Diversity, RAPD, Saccharum sp., Sugarcane
Keywords: Dendrogram; Germ plasm; Saccharum; Primer (cosmetics); Molecular marker; Genetic distance; Sugarcane Cultivation and Processing